Dietary gelatin enhances non-heme iron absorption possibly via regulation of systemic iron homeostasis in rats. (August 2019) - Wu, Lingyu; Zou, Yaqun; Miao, Yu; Zhang, Jiayou; Zhu, Suqin; Zeng, Mingyong; Wu, Haohao
Graphical abstract: Highlights: Dietary gelatin boosted iron absorption in rat hemoglobin regeneration assays. Gelatin had a weak capacity to solubilize luminal ferric iron during digestion. Prolyl-hydroxyproline is the functional degradation product of dietary gelatin. Prolyl-hydroxyproline decreased hepcidin and increased erythropoietin in plasma. Abstract: Gelatin-based traditional Chinese medicines have long been used to treat anemia. Here, rats on the gelatin-based AIN-93G diet showed higher hemoglobin regeneration efficiencies and liver iron concentrations than those fed the diets based on several other animal proteins from muscle sarcoplasm and fibrils, egg white, whey and casein. However, among these animal proteins, gelatin had the lowest digestibility under simulated gastric-proximal intestinal digestion, and its hydrolysate showed the lowest capacity to aid iron absorption in Caco-2 monolayers via templating ferric oxyhydroxide nanoparticles. In another rat hemoglobin regeneration assay, dietary supplementations with gelatin and its two major degradation products, glycine and prolyl-hydroxyproline, revealed that gelatin boosted iron absorption not through glycine, but rather via prolyl-hydroxyproline, which had inhibitory and stimulatory effects on the plasma levels of hepcidin and erythropoietin, respectively. Dietary gelatin thus seems to enhance non-heme iron absorption via regulating systemic iron homeostasis rather than via solubilizing luminal ferric iron.